The Implementation of Physical Education Learning Evaluation on Junior High School Level - Muksin, Muhammad; Gazali, Novri; D, Daharis (Universitas Pendidikan Indonesia, 2019)
This study was aimed at determining the implementation of evaluation of physical education learning on the Junior High Schools level in Dayun District, Siak Regency. The research was a descriptive research. The data obtained from 12 junior high school physical education teachers in Dayun, Siak Regency. The instrument of this research was a closed questionnaire whose answers had been stated and the respondent had to choose one of the alternative answers using a Likert scale. The conclusion of this study is that the implementation of the evaluation of physical education learning at the junior high school level in Dayun, Siak Regency, has been running very well with the average score of the overall questionnaire is 76.38%.Â Â